Benefitting from globalisation and technological change in Australia - Sila, Urban (OECD Economics Department Working Papers, 2019)
Australia has seen large rises in living standards over the last decades across the whole of the income distribution. Technological change and international trade have contributed to this success, but have also brought structural change. Some industries have declined, while others flourished. Furthermore, new technologies and structural change create new skills and new tasks, boosting demand for some jobs, while making others disappear. Although technology and globalisation have not decreased overall employment, certain people, groups, and communities have undergone disruptive change and experienced falling living standards. Some groups face a higher risk of poverty and laid-off workers can have difficulty finding a new job. Well-informed and well-targeted policy is therefore needed to ensure that the benefits of technology and globalisation are widely shared. This paper focuses on policies to ensure that everyone in Australia has the opportunity to benefit from technological change and globalisation. The paper assesses policies relating to three issues: i) labour markets and active labour market policies; ii) education and skills; to ensure adequate skills for accessing good quality jobs; and iii) urban environments, ensuring that Australia's highly urbanised population can adapt to change